Aromatic polyimides from m-phenylene diamines containing pendant groups: synthesis and characterization - Pal, R. R.; Patil, P. S.; Dere, R. T.; Salunkhe, M. M.; Maldar, Noormahamad N.; Wadgaonkar, P. P. (Journal Applied Polymer Science, 2005)
Two diamine monomers, 4-[4-(1-methyl-1-phenyl)phenoxy]-1,3-(diamino benzene and 4-{-[(4-methylphenyl)sulfonyl]phenoxy}-1,3-diamino benzene, were synthesized, and both diamines were polycondensed with three commercial dianhydrides to obtain aromatic polyimides containing pendant groups. The polyimides were characterized by solubility tests, viscosity measurements, IR, H-1-NMR, and C-13- NMR spectroscopy, x-ray diffraction studies, and thermogravimetric analysis. The polymides had inherent viscosities of 0.33-0.58 dL/g in m-cresol at 30 +/- 0.1 degrees C. All the polyimides were amorphous and were soluble in solvents such as NNdimethylacetamide, N-methyl-2-pyrrolidone, N,N-dimethylformamide, and in-cresol. Thermogravimetric analysis of the polymides indicated no weight loss below 410 degrees C under a nitrogen atmosphere. (c) 2005 Wiley Periodicals, Inc.
Keywords: heteroatom-containing polymers; High performance polymers; polyimides

Synthesis and characterization of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages - Pal, R. R.; Patil, P. S.; Salunkhe, M. M.; Maldar, Noormahamad N.; Wadgaonkar, P. P. (Polymer International, 2005)
A series of aromatic polyamides containing an s-triazine ring with thiophenoxy linkages was synthesized from two new diacids, namely 2,4-bis-(4-carboxyphenoxy)-6-thiophenoxy-s-triazine and 2,4-bis-(3-carboxyphenoxy)-6-thiophenoxy-s-triazine, and commercially available aromatic diamines by using Yamazaki's phosphorylation reaction. The polyamides were obtained in good yields and were characterized by solubility tests, viscosity measurements, FTIR, H-1 and C-13 NMR spectroscopy, X-ray diffraction studies and thermogravimetric analysis. The polyamides were found to have inherent viscosities in the range of 0.35 to 0.56 dl g(-1) in N,N-dimethylacetamide (DMAc) at 30 +/- 0.1 degreesC. All the polyamides were readily soluble in solvents such as DMAc, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF) and m-cresol. Thermogravimetric analysis of the polyamides indicated no weight loss below 345 degreesC under a nitrogen atmosphere. (C) 2004 Society of Chemical Industry.
Keywords: 2; 4-bis-(3/4-carboxyphenoxy)-6-thiophenoxy-s-triazine; direct polycondensation; polyamide; s-triazine ring